Rencana Aksi Nasional Hak Asasi Manusia (RANHAM) 1998-2003: dalam Mewujudkan Masa Reformasi Demokratis - Taufik Hidayat Sitorus; Tiar Meidayani Pasaribu; Dini Latifa Hanum (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
The 1998-2003 National Human Rights Action Draft (RANHAM) was an initiative of the Indonesian government that was launched after a period of political reform in 1998. This RANHAM aims to strengthen the protection and promotion of human rights in post-New Order Indonesia. Some of the main points in the RANHAM include community empowerment, legal reform, eradication of torture, protection of women's and children's rights, and strengthening human rights protection institutions such as Komnas HAM. RANHAM 1998-2003 is part of a broader effort to change the human rights paradigm in Indonesia after the authoritarian era. However, its implementation has not always gone smoothly, and challenges remain in the advancement of human rights in post-Reformasi Indonesia. This paper aims to analyze how the realization of RANHAM 1998-2003 and as a projection in the implementation of RANHAM today to be in accordance with what has been conceptualized from the beginning about RANHAM. The research method used in this paper is a qualitative descriptive research method which is to explain thoroughly about the problem by describing it. The data used in this writing comes from official documents, government evaluation reports and reports of human rights institutions that are collected and analyzed to then be described. In fact, it can be concluded that the RANHAM aims to strengthen the protection and promotion of human rights in Indonesia after the New Order period.